2017
DOI: 10.1371/journal.pone.0185363
|View full text |Cite
|
Sign up to set email alerts
|

Increased cortical porosity and reduced cortical thickness of the proximal femur are associated with nonvertebral fracture independent of Fracture Risk Assessment Tool and Garvan estimates in postmenopausal women

Abstract: The Fracture Risk Assessment Tool (FRAX) and Garvan Calculator have improved the individual prediction of fracture risk. However, additional bone measurements that might enhance the predictive ability of these tools are the subject of research. There is increasing interest in cortical parameters, especially cortical porosity. Neither FRAX nor Garvan include measurements of cortical architecture, important for bone strength, and providing independent information beyond the conventional approaches. We tested the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 32 publications
2
22
0
Order By: Relevance
“…In another study using HR-pQCT and StrAx software, cortical porosity of the inner transitional zone at the ultra-distal radius was associated with incident fracture in postmenopausal women independent of femoral neck (FN) aBMD and FRAX score, but only marginally after adjustment for ultra-distal radius aBMD [19]. Our research group has previously reported that increased cortical porosity at the proximal femur was associated with fracture independent of FN aBMD and FRAX [15,20].…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…In another study using HR-pQCT and StrAx software, cortical porosity of the inner transitional zone at the ultra-distal radius was associated with incident fracture in postmenopausal women independent of femoral neck (FN) aBMD and FRAX score, but only marginally after adjustment for ultra-distal radius aBMD [19]. Our research group has previously reported that increased cortical porosity at the proximal femur was associated with fracture independent of FN aBMD and FRAX [15,20].…”
Section: Introductionmentioning
confidence: 83%
“…Using a cortical porosity threshold >80 th percentile identified 20% additional fracture cases who were unidentified by FRAX, and improved the net reclassification of fracture cases [20]. This suggests that a measurement of cortical porosity captures other important skeletal properties not captured by the FRAX score.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations